Review of fecal microbiota transplantation in autistic children and feasible techniques for fecal microbiota transplant delivery - Darina Malygina, Alexander Volkov, Olga Zhukova, Olga Vorobyova, Dmitry Panteleev, Daria Zykova, Anna Blagonravova (Journal of Applied Pharmaceutical Science, 2022)
The review considers the implementation of fecal microbiota transplantation (FMT) to treat several kinds of diseases such as gastrointestinal disorders, diabetes mellitus, metabolic syndrome, and others. The use of FMT in the treatment of neurological disorders such as autism spectrum disorders in children is considered in more detail. We compared the techniques used to deliver FMTs, such as capsules, enemas, introduction through upper gastrointestinal tract, and colonoscopy. This article demonstrates various approaches to the preparation of capsules with lyophilisate of FMTs, such as suspending, microencapsulation, and use of capsule-in-a-capsule technology. These techniques are designed to protect the fecal microbiota microorganisms from the acidic pH of the gastric juice.
Keywords: Fecal microbiota transplantation, autism spectrum disorders, capsules